Milk fat globule membrane promotes brain development in piglets by enhancing the connection of white matter fiber trace - Zhang, Yingqian; Zhao, Bangcheng; Man-Yau, Szeto Ignatius; Pan, Zhixiang; Gao, Lijuan; Li, Qinxi; Tang, Cheng; Wang, Yu; Tang, Xun; Zhao, Zifu; Hao, Jingyu; Duan, Sufang; et al. (Frontiers in Nutrition, 2023)
Brain development during infancy is crucial for later health and development. For neonates who cannot receive exclusive breast milk, infant formula becomes a vital source of nutrition. Although Milk Fat Globule Membrane (MFGM) has been demonstrated to enhance brain development, the optimal dose requires further investigation. In this study, eighty piglets aged two days were randomly assigned to four groups according to the dietary formula: basal diet (Control), 1.74 g MFGM per 100 g diet (MFGM-L), 4.64 g MFGM per 100 g diet (MFGM-M), and 6.09 g MFGM per 100 g diet (MFGM-H). The piglets' daily body weight and milk intake were measured until 31 days postnatal. Learning and memory abilities were evaluated on day 15 through the spatial T-maze test. Furthermore, we also used MRI to analyze functional and structural changes in brain tissues. At last, mRNA and protein expression of brain-derived neurotrophic factor (BDNF) and neurotrophin-3 (NTF-3) in the hippocampus and prefrontal cortex were evaluated. The results indicated that MFGM supplemented diet significantly improved the piglets' accuracy in the T-maze test, with MFGM-L performing the best. MRI showed no volumetric differences in the gray and white matter within the groups. However, the fractional anisotropy in the left and right hippocampus of piglets in the MFGM-L group was much higher than in the other three groups. In addition, there was a strong correlation between the performance of the T-maze test accuracy and the hippocampal fractional anisotropy. The MFGM supplemented diet increased the expression of BDNF in the cerebral cortex, but changes in BDNF weren't consistent with the results of the T-maze test. In conclusion, adding 1.74 g MFGM per 100 g diet can significantly improve neonatal piglets' learning and memory abilities, probably by enhancing the connection of white matter fiber bundles in the brain.